Halal science: synergizing opportunities / E. Tavasuria Elangovan - Elangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
Faculty of Applied Sciences organized an Industry Collaboration Visit to Wisma FMM with the Federation of Malaysian Manufacturers of Malay-sian Food Manufacturing Group (FMM-MAFMAG). The strategic partnership was aimed at forming a collaboration in the development of the newly proposed Bachelor Degree in Halal Science programme. This industry collaboration involved six members of Federation of Malaysian Manu-facturers of Malaysian Food Manufacturing Group namely, En. Sariffuddin Mahmud, Nestle Halal Operations Manag-er, Pn. Nurul Husna Ahmad Ripaai, Nestle Halal Develop-ment Manager, En. Wan Ahmad Syazwan Mohamed, Dutch Lady Regulatory Affairs & Halal Manager, En. Zulkefli Kasri, Ajinamoto Head Specialist of Corporate Affairs Department, En. Akhtar Hisseini Mohd Nor, Head of Halal Affairs, F&N Beverages Intuitional Support & Sourcing and En. Ahmad Syukry Ibrahim, Mamee-Double Decker Manager of Islamic Affairs & Government Relation.